ANALISIS PELAKSANAAN MANAJEMEN LOGISTIK DAN PERALATAN PENANGGULANGAN BENCANA DI BPBD KABUPATEN BONE BOLANGO - Nur Asiah (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The aim of this research is to analyze how logistics management and disaster management are implemented in Bone Bolango Regency. This research is descriptive qualitative research which aims to interpret a phenomenon being studied. Data source sampling was carried out using purposive sampling. The sample in this study was the Head of Logistics and Equipment Division, Logistics Distribution Section, and Data and Information Section of BPBD Bone Bolango Regency. Bone Bolango Regency is one of the disaster-prone areas in Gorontalo Province. One of the activities carried out by BPBD in this case is providing logistical assistance and disaster management equipment to communities affected by disasters. Logistics and disaster management equipment are managed in logistics management. This research was conducted at BPBD Bone Bolango Regency in 2022. The results of this research show that logistics management and disaster management equipment at BPBD Bone Bolango Regency has been implemented, but not as it should be. Improvements can be made by providing good warehouse facilities, procuring tank cars, and increasing human resources for disaster operators.